PROBLEMATIKA SISTEM PEMBELAJARAN SALAFIYAH DI PONDOK PESANTREN SHUFFAH HIZBULLAH DUSUN OLI DESA DESA HITU KABUPATEN MALUKU TENGAH - Saida Manilet (Al-Iltizam, 2020)
Abstract: The purpose of this study was to obtain information regarding the salafiyah learning system in the Shuffah Hizbullah Islamic boarding school along with the basic problems that resulted in the community of Oli hamlet not involving their children in the system. This type of research is ex post facto with a qualitative approach. In this study, the data collection techniques used were observation, interview and documentation. The data is then reduced according to the focus of the study, after which it is presented in a narrative form and ends with drawing conclusions. The results of the study found that the salafiyah learning system in Dusun Oli, Hitu Village, Leihitu District still uses classical models and methods that have not been touched by modern things. However, the evaluation to measure the success of the objectives has not been carried out properly. In addition, the people of Dusun Oli generally like learning salafiyah, but what is a factor in the participation of students from Hamlet Oli in learning salafiyah is due to 5 things, namely 1) Parents' lack of understanding about salafiyah subjects and the benefits of learning them. This is because there is no clear socialization from the pesantren, 2) The opportunity to become the TNI that was promised by the pesantren to ordinary students other than boarding students causes parents to feel sufficient if their child only studies at the madrasa in the morning, 3) Parents' busyness causes the child participate in helping their work, 4) There is no obligation given to all students in the Islamic Boarding School to take part in salafiyah lessons, 5) Lack of parental trust to allow children to study in the pesantren in the afternoon and evening.